The Association between Clinical Features and Measurements of Intra-Compartmental Pressure in Diagnosis of Acute Compartment Syndrome of Closed Leg Fractures - Jaff, Hamid Ahmad Mahmud (Sulaimani Journal for Pure and Applied Sciences, 2021)
Objective: To find the clinical features of compartment syndrome and measurement of intra-compartmental pressure (ICP) in early diagnosis of the compartment syndrome of different types of closed leg bone fractures and their association with the severity of the fracture. Methodology: This prospective study included 20 patients with unilaterally closed fractures of the tibia and/or fibular fracture that presented to Shar Hospital, Sulaimaniyah City, Northern Iraq, from October 1st, 2018, to July 1st, 2020. Sociodemographic information with date and mechanism of injury, severity, side, and site of a fractured leg, and fracture's type according to Oestern and Tscherne classification of the close fracture were obtained. ICP was measured in the broken leg and normal leg at the time of admission to the emergency ward for patients using the needle-infusion technique (Whiteside's technique). Results: All patients were followed clinically by looking at features of the compartment for three days before the definitive treatment was established. We found that 8 out of 20 patients were complaining of severe, unusual pain (paresthesia) during follow-up. Acute compartment syndrome (ACS) was diagnosed in 1 (55-year-old man) out of 8 patients whose clinical features of compartment syndrome built up and with the differential pressure (∆p) of <30 mmHg. The cause of his fracture was a road traffic accident (RTA), and he underwent a fasciotomy. At the same time, the rest of the patients had no features of the compartment. Conclusions: We revealed a significant clinical correlation between the measurement of ICP and early detection and diagnosis of the post-traumatic ACS of the leg, and the measurement of ICP was valuable in the diagnosis of ACS and as a criterion for decompression. Also, this study shows a positive correlation between the type of fracture according to the Oestern and Tscherne classification and the increase in the measurement of the ICP.
Keywords: Prospective study; Whiteside's technique; Intra-compartmental pressure; Acute compartment syndrome; Closed leg fractures